Nickel-iron-manganese layered oxide and preparation method and application thereof
A method for preparing nickel-iron-manganese layered oxides with even sodium distribution and structural support addresses sodium loss and residual alkali issues, enhancing the performance of sodium ion batteries.
Patent Information
- Application Number
- CN202310237987.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-14
AI Technical Summary
Sodium-nickel-iron-manganese layered oxides used in sodium-ion batteries face issues with sodium loss at high calcination temperatures, leading to residual alkali formation, poor processing capabilities, and reduced cycle life due to uneven sodium distribution and high sodium carbonate melting points.
A method involving a liquid phase mixing of sodium and precursor particles with a thickener to evenly distribute sodium, reducing calcination temperature and time, and using a thickener to prevent agglomeration, enhancing structural stability and conductivity.
The method results in a nickel-iron-manganese layered oxide with high electrochemical activity, low surface residual alkali, and improved cycle stability, offering a sodium ion battery with high specific capacity and good cycle stability.
Smart Images

Figure CN116282222B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a nickel-iron-manganese layered oxide and a preparation method and application thereof. Background Art
[0002] In recent years, energy storage devices represented by lithium-ion batteries have been widely used in small electronic products and continue to grow rapidly in the new energy vehicle and energy storage industries. However, lithium resources, as core raw materials, have become an important factor affecting their development due to supply and demand mismatches and economic issues. Sodium resources are abundant and evenly distributed. Sodium-ion batteries produced with them as raw materials are basically the same as lithium-ion batteries in terms of working principles and production processes, and are better in low-temperature performance, rate performance and economy. However, their cycle life and energy density are inferior to lithium-ion batteries. They can be an effective supplement to lithium-ion batteries in the fields of energy storage and some passenger cars and two-wheeled vehicles.
[0003] Sodium-nickel-iron-manganese layered oxides as positive electrode materials for sodium-ion batteries have high energy density and stable crystal structure, and can be adapted to the existing synthesis route of lithium battery ternary materials. They can quickly enter the market and therefore have attracted widespread attention. However, in the process of preparing sodium-nickel-iron-manganese layered oxides, due to the high melting point of sodium carbonate, the temperature in the calcination stage is as high as 900°C, resulting in the loss of sodium in the material. In order to replenish the sodium element lost at high temperature, excessive sodium salt (>1.05) is often added during sodium mixing, resulting in residual and uneven distribution of sodium salt on the surface of the material after sintering, and combined with CO2 and moisture in the air, in the form of sodium carbonate and sodium hydroxide to form residual alkali on the surface of the material, which in turn leads to poor subsequent processing capabilities of the material, increased irreversible capacity loss, and greatly reduced cycle life. Summary of the invention
[0004] The purpose of the present invention is to provide a nickel-iron-manganese layered oxide and a preparation method and application thereof. The nickel-iron-manganese layered oxide provided by the present invention has the advantages of high electrochemical activity, good structural stability and low surface residual alkali, and the prepared sodium ion battery has good cycle stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing nickel-iron-manganese layered oxide, comprising the following steps:
[0007] dissolving a thickener in a solvent to obtain a thickener solution;
[0008] Ni x Fe y Mn z (OH)2 and a sodium source are mixed with the thickener solution to obtain a precursor slurry; Na and Ni in the sodium sourcex Fe y Mn z The molar ratio of (OH)2 is 0.98 to 1.03:1;
[0009] The precursor slurry is dried and calcined in sequence to obtain the nickel-iron-manganese layered oxide; the calcination temperature is 600-850° C., and the holding time is 6-15 hours;
[0010] The chemical composition of the nickel-iron-manganese layered oxide is shown in Formula 1: NaNi x Fe y Mn z O2 formula 1; in formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
[0011] Preferably, the thickener is one or more of citric acid, glucose, sucrose, carboxymethyl cellulose, acrylic acid, polyacrylate and polyurethane.
[0012] Preferably, the solvent is water or a water-ethanol mixed solvent, and the volume content of ethanol in the water-ethanol mixed solvent is less than 20%.
[0013] Preferably, the Ni x Fe y Mn z (OH)2 was prepared by coprecipitation.
[0014] Preferably, the sodium source is one or more of sodium hydroxide, sodium carbonate, sodium oxalate, sodium chloride and sodium nitrate.
[0015] Preferably, the calcination is performed in an air atmosphere or an oxygen atmosphere.
[0016] Preferably, the mass concentration of the thickener solution is 1-10%.
[0017] Preferably, the solid content of the precursor slurry is 30-80%, and the viscosity is 1000-10000 mPa·s.
[0018] The present invention provides a nickel-iron-manganese layered oxide prepared by the preparation method described in the above scheme, having a chemical composition shown in Formula 1: NaNi x Fe y Mn z O2 formula 1; in formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
[0019] The present invention provides the use of the nickel-iron-manganese layered oxide described in the above scheme as a positive electrode material in a sodium ion battery.
[0020] The invention provides a method for preparing nickel-iron-manganese layered oxide, comprising the following steps: dissolving a thickener into a solvent to obtain a thickener solution; x Fe y Mn z (OH)2 and a sodium source are mixed with the thickener solution to obtain a precursor slurry; Na and Ni in the sodium source x Fe y Mn z The molar ratio of (OH)2 is 0.98 to 1.03:1; the precursor slurry is dried and calcined in sequence to obtain the nickel-iron-manganese layered oxide; the calcination temperature is 600 to 850°C, and the insulation time is 6 to 15 hours; the chemical composition of the nickel-iron-manganese layered oxide is shown in Formula 1: NaNi x Fe y Mn z O2 formula 1; in formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
[0021] The present invention adopts a liquid phase method to mix sodium, so that the sodium element is evenly distributed on the precursor particles, and it is easier to enter the interior of the material during the calcination stage, which is beneficial to reduce the calcination temperature and shorten the calcination time, thereby reducing the loss of the sodium element at high temperature; the present invention introduces a thickener to prevent the particles from agglomerating and settling during the drying process of the slurry, and plays a better role in fixing the sodium source; the precursor Ni is filled with x Fe y Mn z The thickener in the pores of the (OH)2 particles only has some carbon remaining after calcination, which can increase the conductivity of the material on the one hand, and support the physical structure of the particles on the other hand, thereby enhancing the structural stability of the material. The sodium ion battery prepared using the nickel-iron-manganese layered oxide of the present invention as the positive electrode material has a high specific capacity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The NaNi prepared in Example 1 0.4 Fe 0.2 Mn 0.4 SEM image of O2 particles;
[0023] Figure 2 Ni prepared in Example 1 0.4 Fe 0.2 Mn 0.4 SEM image of the (OH)2 particle surface;
[0024] Figure 3 This is a SEM image of the particle surface of the precursor slurry prepared in Example 1 after drying and crushing;
[0025] Figure 4 The NaNi prepared in Example 1 0.4 Fe 0.2 Mn 0.4 SEM image of the surface of O2 particles;
[0026] Figure 5 The XRD pattern of the nickel-iron-manganese layered oxide prepared in Example 1;
[0027] Figure 6 This is a SEM image of the surface of the nickel-iron-manganese layered oxide particles prepared in Comparative Example 1;
[0028] Figure 7 The XRD pattern of the nickel-iron-manganese layered oxide prepared in Comparative Example 1;
[0029] Figure 8 This is the 1C cycle test life curve of the positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing nickel-iron-manganese layered oxide, comprising the following steps:
[0031] dissolving a thickener in a solvent to obtain a thickener solution;
[0032] Ni x Fe y Mn z (OH)2 and a sodium source are mixed with the thickener solution to obtain a precursor slurry; Na and Ni in the sodium source x Fe y Mn z The molar ratio of (OH)2 is 0.98 to 1.03:1;
[0033] The precursor slurry is dried and calcined in sequence to obtain the nickel-iron-manganese layered oxide; the calcination temperature is 600-850° C., and the holding time is 6-15 hours;
[0034] The chemical composition of the nickel-iron-manganese layered oxide is shown in Formula 1: NaNi x Fe y Mn z O2 formula 1; in formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
[0035] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0036] The present invention dissolves the thickener into the solvent to obtain a thickener solution.
[0037] In the present invention, the thickener is preferably one or more of citric acid, glucose, sucrose, carboxymethyl cellulose, acrylic acid, polyacrylate and polyurethane; the solvent is preferably water or a water-ethanol mixed solvent; when the solvent is a water-ethanol mixed solvent, the volume content of ethanol in the water-ethanol mixed solvent is preferably below 20%, more preferably 5-20%, and further preferably 8-15%.
[0038] In the present invention, the mass concentration of the thickener solution is preferably 1-10%, more preferably 2-8%, and further preferably 3-6%. In the present invention, the thickener can prevent the particles of the slurry from agglomerating and settling during the drying process, and play a better role in fixing the sodium source.
[0039] After obtaining the thickener solution, the present invention further comprises Ni x Fe y Mn z (OH)2 and a sodium source are mixed with the thickener solution to obtain a precursor slurry.
[0040] In the present invention, the Ni x Fe y Mn z (OH)2 is preferably prepared by coprecipitation; the coprecipitation method is used to prepare Ni x Fe y Mn z (OH)2 preferably comprises the following steps:
[0041] The nickel salt, ferrous salt, manganese salt, precipitant and complexing agent are mixed to perform a coprecipitation reaction to obtain the Ni x Fe y Mn z (OH)2.
[0042] In the present invention, the nickel salt preferably includes nickel sulfate; the ferrous salt preferably includes ferrous sulfate; the manganese salt preferably includes manganese sulfate; the precipitant preferably includes sodium hydroxide solution; and the complexing agent is preferably an aqueous ammonia solution.
[0043] In the present invention, the molar ratio of Ni in the nickel salt, Fe in the ferrous salt and Mn in the manganese salt is x:y:z, 0<x<0.5, 0<y<0.33, 0<z<0.5, and x+y+z=1.
[0044] In the present invention, the amount of the ammonia solution is preferably such that the NH3 concentration in the reaction system is 5 to 10 g / L; the amount of the precipitant is preferably such that the pH value of the reaction system is maintained at 10 to 12.
[0045] In the present invention, the coprecipitation reaction is preferably carried out at 50-65°C. The present invention has no special requirements on the time of the coprecipitation reaction. x Fe y Mn z The particle size D50 of (OH)2 is preferably 5 to 15 μm, more preferably 10 μm.
[0046] After the coprecipitation reaction is completed, the product is preferably aged, washed, filtered, dried and crushed in sequence to obtain the Ni x Fe y Mn z (OH)2.
[0047] In the present invention, the Ni x Fe y Mn z The porosity of (OH)2 is preferably 5 to 15%, more preferably 10 to 13%. x Fe y Mn z The morphology of (OH)2 is spherical secondary particles with a porous structure, which are composed of nanosheets extending outward from the center of the particle.
[0048] In the present invention, the sodium source is preferably one or more of sodium hydroxide, sodium carbonate, sodium oxalate, sodium chloride and sodium nitrate. x Fe y Mn z The molar ratio of (OH)2 is 0.98 to 1.03:1, preferably 0.99 to 1.02:1, and more preferably 1.00 to 1.01:1.
[0049] In the present invention, the amount of the thickener solution is preferably such that the solid content of the precursor slurry reaches 30 to 80%, more preferably 40 to 70%, and further preferably 50 to 60%.
[0050] In the present invention, the mixing preferably includes one or more of mechanical stirring, ball milling and grinding.
[0051] In the present invention, the viscosity of the precursor slurry is preferably 1000 to 10000 mPa·s, more preferably 3000 to 8000 mPa·s, and further preferably 5000 to 6000 mPa·s.
[0052] After obtaining the precursor slurry, the present invention sequentially dries and calcines the precursor slurry to obtain the nickel-iron-manganese layered oxide.
[0053] In the present invention, the drying can be any drying method, as long as the moisture content of the material after drying is less than 1%. x Fe y Mn z Part of the pores on the surface of the (OH)2 particles are filled with the sodium source and the thickener, and the porosity is 1 to 10%.
[0054] Before the calcination, the dried precursor is preferably crushed. The present invention has no special requirements for the crushing process, and a conventional crushing process can be used.
[0055] In the present invention, the calcination temperature is 600-850°C, preferably 650-800°C, more preferably 700-750°C; the calcination holding time is preferably 6-15h, more preferably 8-13h, and further preferably 10-11h. In the present invention, the calcination is preferably carried out in an air atmosphere or an oxygen atmosphere.
[0056] In the calcination process of the present invention, the sodium source enters the Ni x Fe y Mn z (OH)2, forming a chemical formula of NaNi x Fe y Mn z Nickel-iron-manganese layered oxides filled with Ni x Fe y Mn z After calcination, only some carbon remains in the pores of the (OH)2 particles, which can increase the conductivity of the material on the one hand and support the physical structure of the particles on the other hand, thereby enhancing the structural stability of the material.
[0057] The present invention provides a nickel-iron-manganese layered oxide prepared by the preparation method described in the above scheme, having a chemical composition shown in Formula 1: NaNi x Fe y Mn z O2 formula 1; in formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
[0058] The nickel-iron-manganese layered oxide of the present invention is mixed with sodium by a liquid phase method, so that the sodium element is evenly distributed on the precursor particles, and is more likely to enter the interior of the material during the calcination stage, which is beneficial to reducing the calcination temperature and shortening the calcination time, thereby reducing the loss of the sodium element at high temperature, and thus there is no need to add a large amount of excess sodium salt, thereby reducing the residual alkali content on the surface of the nickel-iron-manganese layered oxide; the thickener is introduced into the present invention to prevent the particles from agglomerating and settling during the drying process of the slurry, thereby playing a better role in fixing the sodium source; the thickener filled in the precursor Ni x Fe y Mnz The thickener in the pores of the (OH)2 particles only has some carbon left after calcination, which can increase the conductivity of the material on the one hand, and support the physical structure of the particles on the other hand, thereby enhancing the structural stability of the material. The sodium ion battery prepared using the nickel-iron-manganese layered oxide of the present invention as the positive electrode material has a high specific capacity and good cycle stability.
[0059] The present invention provides the use of the nickel-iron-manganese layered oxide described in the above scheme as a positive electrode material in a sodium ion battery.
[0060] The nickel-iron-manganese layered oxide provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0061] Example 1
[0062] The chemical formula for preparing nickel-iron-manganese layered oxide is NaNi 0.4 Fe 0.2 Mn 0.4 O2, the preparation method is as follows:
[0063] 1) nickel sulfate, ferrous sulfate and manganese sulfate are selected as reaction raw materials, according to the molar ratio of Ni, Fe and Mn being 4:2:4, the precipitant is selected as sodium hydroxide solution, the complexing agent is selected as ammonia solution, and the coprecipitation reaction is carried out in a coprecipitation reactor, the reaction temperature is 60°C, the pH is controlled to 10.5, the ammonia concentration is controlled to 8g / L, and the feeding is stopped when the particle size grows to 10μm, and Ni is obtained after aging, washing, filtering, drying and crushing. 0.4 Fe 0.2 Mn 0.4 (OH)2;
[0064] 2) The thickener is selected as carboxymethyl cellulose and the solvent is selected as water, and a thickener solution with a mass fraction of carboxymethyl cellulose of 5% is prepared;
[0065] 3) According to the sodium and Ni in the sodium source 0.4 Fe 0.2 Mn 0.4 The molar ratio of (OH)2 is 1.01:1. Sodium carbonate and Ni 0.4 Fe 0.2 Mn 0.4 (OH)2 is added to the thickener solution in step 2) and mechanically stirred to form a precursor slurry with a solid content of 65% and a slurry viscosity of 8300 mPa·s;
[0066] 4) The precursor slurry in step 3) is dried, crushed, and then calcined in a blast box atmosphere furnace at a temperature of 800° C. for 10 h, and then naturally cooled to room temperature to obtain NaNi0.4 Fe 0.2 Mn 0.4 O2 layered oxide positive electrode material.
[0067] After testing, Ni 0.4 Fe 0.2 Mn 0.4 The porosity of (OH)2 particles is 13.6%, and the porosity of particles after filling with sodium source and thickener is 3.0%. 0.4 Fe 0.2 Mn 0.4 The compressive strength of (OH)2 particles is 17.6Mpa, and the compressive strength of the particles after calcination is 78.4Mpa.
[0068] Example 2
[0069] The chemical formula for preparing nickel-iron-manganese layered oxide is NaNi 0.33 Fe 0.33 Mn 0.33 O2, the preparation method is as follows:
[0070] 1) nickel sulfate, ferrous sulfate and manganese sulfate are selected as reaction raw materials, the molar ratio of Ni, Fe and Mn is 1:1:1, the precipitant is sodium hydroxide solution, the complexing agent is ammonia solution, and the coprecipitation reaction is carried out in a coprecipitation reactor. The reaction temperature is 60°C, the pH is controlled to 10.2, and the ammonia concentration is controlled to 8g / L. When the particle size grows to 10μm, the feeding is stopped, and Ni is obtained through aging, washing, filtering, drying and crushing. 0.33 Fe 0.33 Mn 0.33 (OH)2;
[0071] 2) The thickener is selected as carboxymethyl cellulose and the solvent is selected as water, and a thickener solution with a mass fraction of carboxymethyl cellulose of 5% is prepared;
[0072] 3) According to the molar ratio of sodium in the sodium source to the precursor being 1.01:1, weigh a certain amount of sodium carbonate and Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 is added to the mixed solution in step 2) and mechanically stirred to form a precursor slurry with a solid content of 60% and a slurry viscosity of 7100 mPa·s;
[0073] 4) The precursor slurry in step 3 is dried, crushed, and then calcined in a blast box atmosphere furnace at a temperature of 800° C. for 10 h, and then naturally cooled to room temperature to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O2 layered oxide positive electrode material.
[0074] After testing, Ni 0.33 Fe 0.33 Mn 0.33 The porosity of (OH)2 particles is 12.3%, and the porosity of particles after filling with sodium source and thickener is 2.1%. 0.33 Fe 0.33 Mn 0.33 The compressive strength of (OH)2 particles is 21.5 MPa, and the compressive strength of the calcined particles is 83.8 MPa.
[0075] Example 3
[0076] Prepare NaNi according to the method of Example 1 0.4 Fe 0.2 Mn 0.4 O2, the difference is that the thickener in step 2) is selected as glucose, the mass fraction of glucose in the thickener solution is 10%, the solid content of the precursor slurry in step 3) is 80%, and the slurry viscosity is 6700mPa·s.
[0077] After testing, the porosity of the particles of Example 3 after being filled with the sodium source and the thickener was 1.4%, and the compressive strength of the particles after calcination was 92.4 MPa.
[0078] Example 4
[0079] Prepare NaNi according to the method of Example 1 0.4 Fe 0.2 Mn 0.4 O2, the difference is that the solvent in step 2) is a mixture of water and ethanol, and the volume ratio is 95:5, and the viscosity of the precursor slurry obtained in step 3) is 6600mPa·s.
[0080] After testing, the porosity of the particles of Example 4 after being filled with the sodium source and the thickener was 1.1%, and the compressive strength of the particles after calcination was 102.1 MPa.
[0081] Comparative Example 1
[0082] The chemical formula for preparing nickel-iron-manganese layered oxide is NaNi 0.4 Fe 0.2 Mn 0.4 O2, the preparation method is different from that of Example 1 in that the sodium source and Ni 0.4 Fe 0.2 Mn 0.4 (OH)2 mixed, that is, according to the sodium and Ni in the sodium source 0.4 Fe 0.2 Mn 0.4 The molar ratio of (OH)2 is 1.01:1. Sodium carbonate and Ni 0.4Fe 0.2 Mn 0.4 (OH)2, mixed evenly in a high-speed mixer and then placed in a box-type atmosphere furnace for calcination, and the subsequent steps are consistent with Example 1.
[0083] After testing, the sodium source and Ni 0.4 Fe 0.2 Mn 0.4 The porosity of the particles after (OH)2 mixing is 12.7%, and the compressive strength of the particles after calcination is 47.8 MPa.
[0084] Comparative Example 2
[0085] Prepare NaNi according to the method of Example 1 0.4 Fe 0.2 Mn 0.4 O2, except that, in step 2), no thickener, i.e., sodium carbonate and Ni 0.4 Fe 0.2 Mn 0.4 (OH)2 was mixed and stirred in water, and the subsequent steps were the same as in Example 1.
[0086] The experiment found that Ni 0.4 Fe 0.2 Mn 0.4 After the stirring of (OH)2 and sodium source in water stops, stratification can be seen soon. 0.4 Fe 0.2 Mn 0.4 The porosity of the particles after (OH)2 mixing is 10.8%, and the compressive strength of the particles after calcination is 56.7 MPa.
[0087] Comparative Example 3
[0088] Prepare NaNi according to the method of Example 1 0.4 Fe 0.2 Mn 0.4 O2, the difference is that the sodium carbonate and Ni added in step 3) are reduced 0.4 Fe 0.2 Mn 0.4 The mass of (OH)2, that is, the solid content of the precursor slurry is reduced to 20%, and the subsequent process is consistent with Example 1.
[0089] After testing, the sodium source and Ni 0.4 Fe 0.2 Mn 0.4 The porosity of the particles after (OH)2 mixing is 4.3%, and the compressive strength of the particles after calcination is 51.6 MPa.
[0090] Comparative Example 4
[0091] Prepare NaNi according to the method of Example 1 0.4 Fe 0.2 Mn 0.4 O2, the difference is that the molar ratio of sodium in the sodium source to the precursor is 1.05:1, and the subsequent process is consistent with Example 1.
[0092] After testing, the sodium source and Ni 0.4 Fe 0.2 Mn 0.4 The porosity of the particles after (OH)2 mixing is 2.7%, and the compressive strength of the particles after calcination is 81.3 MPa.
[0093] The Ni obtained in step 1) of Example 1 was analyzed by field emission scanning electron microscopy (SEM) (JSM-7800F). 0.4 Fe 0.2 Mn 0.4 (OH)2, the precursor slurry obtained in step 3) after crushing the particles and the NaNi obtained in step 4) 0.4 Fe 0.2 Mn 0.4 The particles and surface morphology of O2 layered oxides are tested, such as Figures 1 to 4 As shown. It can be seen that the Ni 0.4 Fe 0.2 Mn 0.4 (OH)2 is a spherical secondary particle with a porous structure, and the primary particle is flaky in shape. After being filled with a sodium source and a thickener, the pores between the primary particles are covered. After calcination, it becomes a spherical particle with a polycrystalline structure and a uniform particle size distribution.
[0094] NaNi prepared in Comparative Example 1 0.4 Fe 0.2 Mn 0.4 The surface of the O2 layered oxide particles was characterized by SEM. Figure 6 As shown, the secondary particles have no specific morphology and the particle structure collapses, which is not conducive to the processing performance of the material.
[0095] The NaNi obtained in Example 1 and Comparative Example 1 were analyzed by XRD diffractometer (Holland Panalytical X'PERT PRO MPD). 0.4 Fe 0.2 Mn 0.4 The physical structure of O2 layered oxide cathode material was tested. The results are as follows Figure 5 , 7 As shown, the XRD spectrum of the material prepared in Example 1 shows that it has higher crystallinity, no impurity phase, and is consistent with the crystal form of the target product, while the XRD spectrum of the material prepared in Comparative Example 1 has poor crystallinity and contains multiple impurity phases.
[0096] The sodium content of the nickel-iron-manganese layered oxides obtained in Examples 1 to 4 and Comparative Examples 1 to 4 was detected using a German SPECTRO ICP-OES plasma emission spectrometer GREEN, and the loss of sodium was obtained. The results are listed in Table 1.
[0097] Table 1 Sodium loss rate of the embodiments and comparative examples
[0098] category Sodium content / Atom.% Sodium loss rate / % Example 1 25.03 0.22% Example 2 25.12 0.13% Example 3 24.99 0.26% Example 4 25.06 0.19% Comparative Example 1 23.04 2.21% Comparative Example 2 23.47 1.78% Comparative Example 3 24.67 0.58% Comparative Example 4 26.06 0.19%
[0099] It can be seen from Table 1 that the sodium content of the material after calcination using the technical solution of the present invention is relatively higher, which can reduce the loss of sodium element. x Fe y Mn z (OH)2 mixing can better optimize the ratio and calcination process.
[0100] The nickel-iron-manganese layered oxide prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was used as the positive electrode material for the sodium ion battery. It was mixed with SP and PVDF in a mass ratio of 85:10:5 in a drying room with a humidity of less than 10% in NMP, homogenized, and the solid content was controlled at 45%. It was coated on an aluminum foil current collector, vacuum-baked at 110°C for 8 hours, and rolled and punched to obtain a positive electrode sheet for the sodium ion battery. The button half-cell was assembled in an argon-filled glove box. The counter electrode was a metal sodium sheet, the diaphragm used was a PE diaphragm, and the electrolyte was 1 mol / L NaPF6 EC / DMC (volume ratio 1:1). The button battery test equipment was the commercial LAND battery test system of Wuhan Blue Electric Electronics Co., Ltd., and the test temperature was 25°C. The button cell was charged and discharged. The 0.1C capacity test process was 0.1C constant current and constant voltage charging to 4.0V, and 0.1C constant current and constant voltage discharging to 2.0V. The first charge and discharge curve of the material was measured. The 1C cycle test process was 1C constant current and constant voltage charging to 4.0V, and 1C discharging to 2.0V. The cycle life curve was obtained after 100 cycles. The results of the 0.1C capacity test and the 1C cycle 100 capacity retention rate test are listed in Table 2. The 1C cycle test life curve of the positive electrode material prepared in Example 1 is shown in Table 2. Figure 7 shown.
[0101] Table 2 Capacity test and cycle capacity retention test results of the embodiments and comparative examples
[0102]
[0103] It can be seen from Table 2 that the sodium ion battery positive electrode material prepared by the technical solution of the present invention has a higher specific capacity and cycle capacity retention rate. Combined with the morphology and XRD characterization results of Example 1 and the comparative example, the compressive strength of the particles in Comparative Example 1 after calcination is significantly reduced, the structure collapses, the crystallinity is poor, and multiple impurity phases appear, which significantly reduces its electrochemical performance. In Comparative Example 2, without introducing a thickener, the porosity of the particles after the precursor slurry is dried is slightly lower than that of the precursor particles. After calcination, more sodium only remains on the surface of the material without entering the interior of the crystal, forming an impurity phase. In Comparative Example 3, the solid content of the slurry is reduced to 20%, and the low viscosity causes the precursor to settle during the drying process of the slurry. The sodium is unevenly distributed on the surface of the precursor, and more impurity phases are also formed. In Comparative Example 4, an excessive amount of sodium source is added to the sodium source, and residual alkali is formed after calcination, resulting in poor material processing performance and poor cycle stability of the later battery.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing nickel-iron-manganese layered oxide, characterized in that: The following steps are involved: Dissolving a thickener in a solvent to obtain a thickener solution; the thickener is one or more of glucose, sucrose, carboxymethyl cellulose, polyacrylate and polyurethane; Ni x Fe y Mn z (OH)2 and a sodium source are mixed with the thickener solution to obtain a precursor slurry; Na and Ni in the sodium source x Fe y Mn z The molar ratio of (OH)2 is 0.98-1.03:1; the solid content of the precursor slurry is 30-80%, and the viscosity is 1000-10000 mPa·s; The precursor slurry is dried and calcined in sequence to obtain the nickel-iron-manganese layered oxide; the calcination temperature is 600-850° C., and the holding time is 6-15 hours; The chemical composition of the nickel-iron-manganese layered oxide is shown in Formula 1: NaNi x Fe y Mn z O2 Formula 1; in Formula 1, 0<x<0.5, 0<y<0.33, 0<z<0.5, x+y+z=1.
2. The preparation method according to claim 1, characterized in that: The solvent is water or a water-ethanol mixed solvent, and the volume content of ethanol in the water-ethanol mixed solvent is less than 20%.
3. The preparation method according to claim 1, characterized in that: The Ni x Fe y Mn z (OH)2 was prepared by coprecipitation.
4. The preparation method according to claim 1, characterized in that: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium oxalate, sodium chloride and sodium nitrate.
5. The preparation method according to claim 1, characterized in that: The calcination is performed in an air atmosphere or an oxygen atmosphere.
6. The preparation method according to claim 1 or 2, characterized in that: The mass concentration of the thickener solution is 1-10%.
